Between nature and culture: a stone masonry school and walking path at the Strand Street Quarry - Rolando, Jean-Sebastian (School of Architecture, Planning and Geomatics, 2018)
The dissertation design seeks to make present and enhance the inherent qualities of the Stand Street Quarry in order to reintroduce its heritage narratives into the public realm. The proposed intervention aspires to, if anything, subtlety. It seeks to make the value of the histories of the site evident to the user in such a way that they are compelled to find meaning individually, to interact with the site and the landscape in a meaningful and personal manner. Minimalistic design solutions were sought out in order to produce a product scheme that embeds another layer of human intervention in the palimpsestual narrative of the Signal Hill territory.